1998
DOI: 10.5860/crl.59.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Catalogers in Academic Libraries: Their Evolving and Expanding Roles

Abstract: Catalogers in academic libraries who belong to ALA’s Technical Services Division were surveyed to determine if and how their job functions have changed over the past ten years. The 271 respondents indicated a change from print to electronic formats, involvement of nonprofessionals in higher levels of cataloging, a trend toward outsourcing (particularly, copy cataloging and foreign-language materials), and more cataloging of specialized items, audiovisual materials, and digital documents by professional librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Using a different methodology, Lois Buttlar and Rajinder Garcha surveyed 271 catalogers to determine the change they identified in their work activities and roles between 1987 and 1997. 15 More than 90 percent of the respondents reported that the core activities of their jobs re mained the same-descriptive cataloging and the assignment of call numbers and subject headings, activities long associ ated with their careers. However, the cata logers did report that their roles had ex panded to include managerial tasks, the training of others, and the inclusion of electronic materials.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…Using a different methodology, Lois Buttlar and Rajinder Garcha surveyed 271 catalogers to determine the change they identified in their work activities and roles between 1987 and 1997. 15 More than 90 percent of the respondents reported that the core activities of their jobs re mained the same-descriptive cataloging and the assignment of call numbers and subject headings, activities long associ ated with their careers. However, the cata logers did report that their roles had ex panded to include managerial tasks, the training of others, and the inclusion of electronic materials.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…Their findings showed that cataloging members of ALCTS were still involved in descriptive cataloging, subject analysis, and classification in more than 90 percent of the libraries surveyed in 1997. 37 However, since 1987, these members have expanded their cataloging to include audiovisual materials, digital documents, and Internet resources. 38 Participants also commented that education and training in computer technology skills is not keeping pace with the expectations that catalogers have these skills.…”
mentioning
confidence: 99%
“…76 Gatti reported on the rise of the Generation X (born 1966-1976) cataloger as supervisor. 77 This trend, in part, is occurring due to the aging of the cataloger management workforce and to the reluctance of current catalogers to assume supervisory roles.…”
mentioning
confidence: 99%
“…The survey respondents indicated involvement of paraprofessionals in higher leves of cataloging. 11 In 1995, Mohr and Schuneman conducted a survey of the heads of the main cataloging departments of the 119 Association of Research Libraries (ARL) institutions to examine the changing roles of paraprofessionals in original cataloging in ARL libraries. 12 The results of the survey confirmed the continuing changes in assignment of original cataloging responsibilities to paraprofessionals.…”
Section: Literature Reviewmentioning
confidence: 99%